Enrichment of Circular RNA Expression Deregulation at the Transition to Recurrent Spontaneous Seizures in Experimental Temporal Lobe Epilepsy - Gomes-Duarte, Andreia; Bauer, Sebastian; Venø, Morten T.; Norwood, Braxton A.; Henshall, David C.; Kjems, Jørgen; Rosenow, Felix; Vangoor, Vamshidhar R.; Pasterkamp, R. Jeroen (Frontiers in Genetics, 2021)
Mesial temporal lobe epilepsy (mTLE) is a common form of epilepsy and is characterized by recurrent spontaneous seizures originating from the temporal lobe. The majority of mTLE patients develop pharmacoresistance to available anti-epileptic drugs (AEDs) while exhibiting severe pathological changes that can include hippocampal atrophy, neuronal death, gliosis and chronic seizures. The molecular mechanisms leading to mTLE remain incompletely understood, but are known to include defects in post-transcriptional gene expression regulation, including in non-coding RNAs (ncRNAs). Circular RNAs (circRNAs) are a class of recently rediscovered ncRNAs with high levels of expression in the brain and proposed roles in diverse neuronal processes. To explore a potential role for circRNAs in epilepsy, RNA-sequencing (RNA-seq) was performed on hippocampal tissue from a rat perforant pathway stimulation (PPS) model of TLE at different post-stimulation time points. This analysis revealed 218 differentially expressed (DE) circRNAs. Remarkably, the majority of these circRNAs were changed at the time of the occurrence of the first spontaneous seizure (DOFS). The expression pattern of two circRNAs, circ_Arhgap4 and circ_Nav3, was further validated and linked to miR-6328 and miR-10b-3p target regulation, respectively. This is the first study to examine the regulation of circRNAs during the development of epilepsy. It reveals an intriguing link between circRNA deregulation and the transition of brain networks into the state of spontaneous seizure activity. Together, our results provide a molecular framework for further understanding the role and mechanism-of-action of circRNAs in TLE.